ICMS education in Santa Catarina: Contours and implications - Bona, Juliano (Seven Editora, 2024)
The relationship between educational policies, distribution of resources and gains in educational quality is characterized as a challenge for managers in different regions of Brazil. In the State of Santa Catarina, the challenges are no different or less, and it is in this direction that as of 2023 the ICMS Education transfer methodology comes into force. Thus, our objective is to analyze the contours and implications of the new ICMS Education in the State of Santa Catarina. To this end, we describe the historical experience of other states, their initiatives and consequences. Then, we discuss the Santa Catarina model, the methodological contours and its possible implications, establishing, at the same time, a parallel with the experience of the State of Ceará. The experiences were narrated, the contours and implications of ICMS Education in Santa Catarina were thought out, methodologically modeled. From 2023 onwards, we will move on to the next stages of this movement and its transposition to the field of management. DOI:https://doi.org/10.56238/sevened2024.009-010